Analysis Of Implementation Of Compensation Strategy To Support Employee Performance Improvement (PT Doel Sumbang) - Hendro Nurfahmi; Muhammad Bakr Muhlison (International Journal of Economics, Business and Innovation Research, 2024)
Doel Sumbang Company Yogyakarta Branch faces problems in implementing compensation strategies, such as insignificant base salary ratios between the lowest and highest employees, and overtime compensation that causes a decrease in productivity. The unbalanced salary difference between new and old employees, as well as the cash salary payment system that triggers jealousy, contribute to low work motivation. If these issues are not addressed immediately, they can have a negative impact on the company's productivity. Therefore, the main problem raised in this final project is the error in the implementation of compensation strategies that affect employee performance. The main purpose of this research is to find out and analyze the implementation of the company's compensation strategy towards its employees, and find out about how compensation affects employee performance in a company. This research uses descriptive analysis method. The results concluded that the compensation strategy carried out by PT Doel Sumbang Yogyakarta Branch is 2 (two), namely the total compensation strategy and the package compensation strategy. The total compensation strategy consists of basic salary, BPJS Ketenagakerjaan, and sales bonuses/incentives, and the strategy used is effective to support the improvement of employee performance, this is evidenced by the increasing number of transactions from year to year, especially from 2021 to 2023.